If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 6y = 12y Solving 4x + 6y = 12y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6y' to each side of the equation. 4x + 6y + -6y = 12y + -6y Combine like terms: 6y + -6y = 0 4x + 0 = 12y + -6y 4x = 12y + -6y Combine like terms: 12y + -6y = 6y 4x = 6y Divide each side by '4'. x = 1.5y Simplifying x = 1.5y
| -9-9n=-63 | | 118=4x+5x+10 | | -12+5y+7q-2y-5q-21= | | 8+5x=-6+30 | | w^2-22w+121=81 | | -138=-6(7-2v) | | -8-3p=-8(1+8p) | | 8x+3x=8x | | n/3+8=14 | | 129-134= | | 3x-15=X | | -5n-3=-58 | | 18-2g=4j | | 7(4-8r)-r=85 | | N+9=4-5 | | 8X-2(X+9)=X+48 | | 2y+1+4y-3=180 | | F(-2)=2x^2-5x+6 | | 42=2n+8 | | 129+134= | | m/4=1.25 | | -129+134= | | -129F+134F= | | -26+10x+12k-3x-4k-18= | | 3-3(2-4a)=-99 | | 2x-1y=-7 | | -3x-3=-6x+27 | | 6-4lnx=0 | | 6(9x+9)+2x= | | 2x-1/2x=12 | | 50x-69=0 | | 3z-13z=70 |